Influence of political authorities and civil society in the participatorybud- Get - Livia-Corne, Bardonio (2019)
The objective was to know the influence of the current state of the political authorities and civil society in the development of the participatory budget processes of the Huánuco region 2013. Study of quantitative approach non-experimental design; Kind of basic research; Causal explanatory level; Conducted with a population of 775 and 48 authorities, stratified random sampling was used, resulting in the sample size of 200 representatives of civil society and 30 authorities. An instrument was used; the questionnaire for both representatives of civil society and political authorities, which will allow us to know the current level of knowledge of the development of the participatory budget. When applying the Multiple regression model, a coefficient of determination R2 = 0.347 was obtained, which indicates that 34.7% of the participatory budget variable is explained in the model of preparation, coordination and formulation factors. The result of the analysis of variance was significant showing the validity of the model. At a level of significance of 5%, we conclude that civil society and authorities differ significantly and linearly from the level of knowledge in the development of the participatory budget of the municipalities of the provinces of the Huánuco region.